2023
DOI: 10.1111/cup.14441
|View full text |Cite
|
Sign up to set email alerts
|

Adnexotropic and granulomatous mycosis fungoides following TNF‐α inhibitor treatment

Abstract: Recent publications have documented an increased prevalence of cutaneous T-cell lymphoma (CTCL) in patients undergoing tumor necrosis factor alpha (TNF-α) inhibitor therapy. Herein, we present an uncommon manifestation of mycosis fungoides (MF) with unique pathological findings after the initiation of adalimumab therapy for the treatment of psoriasis. One year after starting treatment, the patient noticed a slowly growing, eroded plaque on the left cheek, the biopsy of which demonstrated mixed granulomatous an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 10 publications
(13 reference statements)
0
2
0
Order By: Relevance
“…A meta-analysis showed that treatment with anti-TNFα agents increased the risk of serious infections (OR: 1.72, 95% CI: 1.56-1.90, p < 0.00001) and an increase in cancer risk (OR: 1.36, 95% CI: 1.20-1.53, p < 0.00001), whereas the risk of tuberculosis was not significantly different (Li et al, 2021). Although there was no consensus on the risk of infection associated with anti-TNFα treatments in published clinical trials, post-marketing surveillance and retrospective studies have shown an increased risk of tuberculosis and other granulomatous infections (Wallis et al, 2004;Godfrey and Friedman, 2019;Athimni et al, 2022;Doughty et al, 2023). A meta-analysis carried out in 2006 showed an increase in the risk of malignancies and serious infections in patients treated with infliximab and adalimumab, where a higher dose was associated with increased cancer risk (Galloway et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…A meta-analysis showed that treatment with anti-TNFα agents increased the risk of serious infections (OR: 1.72, 95% CI: 1.56-1.90, p < 0.00001) and an increase in cancer risk (OR: 1.36, 95% CI: 1.20-1.53, p < 0.00001), whereas the risk of tuberculosis was not significantly different (Li et al, 2021). Although there was no consensus on the risk of infection associated with anti-TNFα treatments in published clinical trials, post-marketing surveillance and retrospective studies have shown an increased risk of tuberculosis and other granulomatous infections (Wallis et al, 2004;Godfrey and Friedman, 2019;Athimni et al, 2022;Doughty et al, 2023). A meta-analysis carried out in 2006 showed an increase in the risk of malignancies and serious infections in patients treated with infliximab and adalimumab, where a higher dose was associated with increased cancer risk (Galloway et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…A meta-analysis showed that treatment with anti-TNFα agents increased the risk of serious infections (OR: 1.72, 95% CI: 1.56–1.90, p < 0.00001) and an increase in cancer risk (OR: 1.36, 95% CI: 1.20–1.53, p < 0.00001), whereas the risk of tuberculosis was not significantly different ( Li et al, 2021 ). Although there was no consensus on the risk of infection associated with anti-TNFα treatments in published clinical trials, post-marketing surveillance and retrospective studies have shown an increased risk of tuberculosis and other granulomatous infections ( Wallis et al, 2004 ; Godfrey and Friedman, 2019 ; Athimni et al, 2022 ; Doughty et al, 2023 ). A meta-analysis carried out in 2006 showed an increase in the risk of malignancies and serious infections in patients treated with infliximab and adalimumab, where a higher dose was associated with increased cancer risk ( Galloway et al, 2011 ).…”
Section: Introductionmentioning
confidence: 99%